The Interplay Between Affect, Dog's Physical Activity and Dog–Owner Relationship - Väätäjä, Heli; Majaranta, Päivi; Cardó, Anna Valldeoriola; Isokoski, Poika; Somppi, Sanni; Vehkaoja, Antti; Vainio, Outi; Surakka, Veikko (Frontiers in Veterinary Science, 2021)
Leaving a dog home alone is part of everyday life for most dog owners. Previous research shows that dog-owner relationship has multifarious effects on dog behavior. However, little is known about the interplay between dog-owner relationship, dog’s physical activity, and affective experiences at the time of the owner leaving home and reunion when the owner comes home. In this paper, we explored how the dog’s general (daily, home alone and over the two-week study period) physical activity, and owner’s perceptions of the dog’s affective state were correlated at those particular moments. Nineteen volunteer dog owners had their dogs (N=19) wear two activity trackers (ActiGraph wGT2X-GT and FitBark2) for two weeks 24 hours per day. Prior to the two-week continuous physical activity measurement period, the owners filled in questionnaires about the dog-owner relationship and the dog behavior. In daily questionnaires, owners described and assessed their own and their perception of their dog’s emotion related experiences and dog’s behavior at the moment of separation and reunion. The results indicated that the dog-owner relationship has an interplay with the dog’s mean daily and weekly physical activity levels. An indication of strong emotional dog-owner relationship (especially related to the dog’s attentiveness, continuous companionship, and time spent together when relaxing) correlated positively with the dog’s mean daily activity levels during the first measurement week of the study. Results also suggest that the dog’s mean daily and over the two-week measurement period physical activity correlated the dog’s and owner’s affective experiences as reported by the owner when the dog was left home alone. More research is needed to understand the interplay between affect, dog’s physical activity, dog-owner relationship, and the effects of these factors on and their interplay with the welfare of dogs.